Arabic on the Dahlak Islands (Erittrea) - (:unkn) unknown (My University, 2014)
Colloque (ARCO 2014) : "Arabic in Contact. Linguistic and Sociolinguistic Perpectives" Exemplier distribué lors de ma communication, session "Arabic Based Contact Varieties in Sub-Saharan Africa"La publication de Proceedings est prévue
Keywords: African Research